KAJIAN TOKOH PEMIKIRAN TAFSIR DI INDONESIA (Telaah Metodologi, Kontekstualisasi Terhadap Penafsiran) - Dozan, Wely (Universitas Islam Negeri Raden Intan Lampung, 2020)
Recently, the dynamics and paradigms of the interpretation of the Qur'an are not only carried out by western and eastern thoughts. However, along with the times and the expansion of the epistemology of knowledge so that the interpretation of the Koran continues to experience developments and constructs to do, especially the interpreters and scholars in Indonesia. The focus of research is often, will look at the dynamics of the development of thought in Indonesia by looking at several figures who reconstruct thinking such as, M. Quraish Shihab, Buya Hamka, Nasaruddin Umar who have been developing so far, so that the commentator in Indonesia have made efforts and building arguments through methodology and contextualization in terms of interpretation, research especially looking at the development of interpretations based on gender verses. The research approach is historical-analytical, which examines the historical roots analytically to see the dynamics and diversity of interpretations of the Qur'an, especially in the development of the Indonesian interpretation. The result of the research shows that the interpretation of thought in Indonesia has experienced dynamics and developments. Moreover, when the verses of the Koran are gender-based, the essence of interpretation is as a solution and interpreting a hermeneutic context by weighing fairly by looking at the history of the Koran, not on a textual way of understanding what which appears in the substance of the text.